PENGAWASAN DINAS CIPTA KARYA DAN TATA RUANG KABUPATEN ROKAN HILIR TERHADAP PEMBANGUNAN FISIK (STUDY KASUS PEMBANGUNAN KANTOR CAMAT KUBU BABUSSALAM TAHUN 2014 ) - Wan Fadli; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The results showed that there are some things that impede the supervision of physical development that have an impact on the failure of the project to construct offices, the writer's observation of the surveillance of physical development can be categorized still very poor, because still lacking maximum performance of officers of Settlements and Spatial Rokan Downstream in carrying out surveillance in the physical development Babussalam Kubu district, and there are still factors - factors inhibiting the supervision of the physical development of the district office Babussalam camp, which is still a lack of human resources, funding / costs and infrastructure facilities.In the process Supervision which sets standards, action judgments, take corrective action, and regular reports, based on the writer's observation, the authors assess is still not good, which is the case according to the authors present a problem in conducting surveillance measures or monitoring physical development in Kecamtan stronghold Babussalam rokan downstream district is only done once a month, and the absence of regular reports prepared by the department of copyrighted works and the district spatial rokan downstream towards the execution of physical development projects. So the impact on the failure of the project to construct offices Babussalam camp. Inside factors - factors inhibiting the supervision of the Department of Human Settlements and Spatial districts rokan downstream to the physical development, the constraints in terms of human resources are categorized still lack quality inspectors agency copyrighted works and spatial planning, in terms of salaries inspectors also minimal, and not the facility or vehicle completeness Department in monitoring the physical project to construct offices Babussalam stronghold Rokan Hilir.Keywords: Surveillance Office of Human Settlements and Physical Development